ANALISIS REWORK PADA PROYEK KONSTRUKSI GEDUNG DI KABUPATEN BADUNG - Sutrisna, Nana; Arya Thanaya, I N.; Ketut Sudipta, I Gst (JURNAL SPEKTRAN, 2013)
Rework is unavoidable from the world of construction, Rework can be a devastating effect on the performance and productivity of both the consultant and the contractor. This study aims to determine the main factors causing rework, efforts to reduce rework. The analysis used the analysis Multivariant factor analysis with the help of Statistical Package for Social Science (SPSS) for Windows version 17.0. From the results obtained by factor analysis the main factors causing the occurrence of rework are: aspects of the owner (poor communication, poor coordination, poor information flow), aspects of planning consultants (lack of information in the field, lack of communication, the situation in the picture on the ground is not suitable). aspects of construction management consultants (lack of information in the field, lack of communication, lack of control), aspects of mechanical electrical plumbing contractors (Materials misdirected, MEP staff inexperience, lack of knowledge about the character of the material, the amount of overtime), aspects of the contractor (lack of competence foreman, foreman lack of experience, lack of experience, the quality of labor is bad, the error in interpreting the specification), aspects of operator (poor flow of information, lack of communication, lack of coordination, lack of operator experience). Efforts to systematically reduce rework most effective according to the respondent's answer is: Systematic planning, detailing and describing the project at every stage of the steps to be taken to achieve quality objectives, set standards of communication, coordination and construction project sinkronasi work with all parties involved in the implementation of the project, Constructing specification limits and criteria and quality standards to be used in engineering design, procurement and construction materials.
Keywords: Project, Rework, Key Factors, Reducing rework